Influencing Factors of Impulsive Buying through Positive Emotion and Hedonic Consumption in E-Commerce - Ana Fitriyatul Bilgies; Armanu; JFX. Susanto Soekiman; Sukesi; Aminullah Assagaf (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The rapid growth of digital technology and e-commerce has transformed consumer shopping behavior, shifting purchases from traditional stores to online platforms driven by convenience, promotions, and innovative payment systems. This transformation has also intensified impulsive buying tendencies, particularly with the rise of features such as PayLater that enhance financial flexibility while stimulating spontaneous consumption. This study aims to analyze the factors influencing impulse buying among Shopee users in East Java through positive emotion and hedonic consumption. The examined variables include sales promotion, paylater facility, shopping lifestyle, and price. A quantitative method was applied by distributing questionnaires to 140 respondents. Data were analyzed using path analysis to test relationships among variables. The findings indicate that sales promotion, paylater facility, shopping lifestyle, and price significantly affect both positive emotion and hedonic consumption. Furthermore, positive emotion and hedonic consumption play a crucial role in enhancing consumers’ impulse buying behavior. Among all variables, shopping lifestyle and price show the strongest influence. These results emphasize the importance of promotional strategies, innovative payment facilities, and enjoyable shopping experiences in encouraging impulsive purchases. This research contributes theoretically to consumer behavior studies and provides practical implications for e-commerce practitioners in designing more effective digital marketing strategies.